Development of rapid setting and self-compacting repair concrete - Lu Min Thant; Pennung Warnitchai; Thanakorn Pheeraphan; Raktipong Sahamitmongkol; Anwar, Naveed; Loom Nam Khong Pijai (Greater Mekong Subregion) Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
This thesis was conducted to come up with Rapid Setting and Self-compacting Repair Concrete. The amount of cement, silica fume, and superplasticizer used in this study were carefully chosen based on literature research, pre-screening tests, and recommendation by suppliers to obtain the desired fresh properties of self-compacting concrete and desirable compressive strength at 7 hours. Slump flow test for flowability, V funnel test for viscosity, L box test for passing ability and penetration resistance for setting time were performed to test on fresh characteristics. For hardened properties, compressive strength at 7 hours, bond strength at 7 days, shrinkage at 28 days were checked. Two level full factorial design with center points was utilized as Design of Experiments (DOE) to analyze the results. Water-cement ratio, percentage of expansive additives content and percentage of silica fume content are selected as factors to investigate their effects on fresh and hardened properties of Rapid Setting and Self compacting Repair Concrete. All fresh and hardened characteristics of Rapid Setting and Self Compacting Repair Concrete were significantly influenced by the effect of silica fume except for L box test and free shrinkage test. A higher silica fume and expansive additive gives better results in mechanical properties of Rapid Setting and Self-compacting Repair Concrete. A mockup was performed to check whether the proposed mix design could be utilized on a real site. According to mockup test, Rapid Setting and Self-compacting Repair Concrete can give the good performance without cracking until 28 days and afterwards while the public is successfully using and passing over the repair mockup. As an additional work, Rapid Setting Repair Concrete was also developed and compared with commercial product which is available in Thailand. The developed Rapid Setting Repair Concrete possesses better workability and higher compressive strength at five hours than the commercial product.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Self-consolidating concrete -- Additives